Pengembangan Media Pembelajaran Pop-Up Book Berbasis EtnoSTEM pada Materi Bangun Ruang untuk Meningkatkan Pemahaman Matematis Siswa Kelas IV Sekolah Dasar - Nurul, Nurul Az Zahra; Bramianto Setiawan (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to develop an EtnoSTEM-based Pop-Up Book learning media on the material of cube and beam spaces to improve the mathematical understanding of fourth grade elementary school students. The research method used is research and development (Research and Development) with the ADDIE model (Analysis, Design, Development, Implementation, Evaluation). The research subjects were fourth grade students of SDN Wanajaya 04 Bekasi Regency. The research instruments included expert validation sheets, teacher and student response questionnaires, and mathematical understanding tests. The validation results show that the EtnoSTEM-based Pop-Up Book learning media is in the very feasible category from the aspects of material, language, and media. Student and teacher responses to the use of media are in the very practical category. The test results showed an increase in students' mathematical understanding after using the learning media, with the acquisition of N-Gain scores in the medium to high category. Thus, the EtnoSTEM-based Pop-Up Book media is effectively used in learning building space to improve mathematical understanding of elementary school students.